GE_GERICHTE A/4560/2009 vom 29. Januar 2009 - GE Cour de justice (2009)
; PRÉVOYANCE PROFESSIONNELLE ; PARTAGE(SENS GÉNÉRAL) ; PRESTATION DE LIBRE PASSAGE ; FONCTIONNAIRE ; CAS D'ASSURANCE | LFLP 22; CCS 122; CCS 124